Serving many masters: public accountability in private policy implementation - Thomann, Eva; Hupe, P. L.; Sager, Fritz (Governance, 2018)
In recent decades, the introduction of market principles has transformed public service delivery into a hybrid. However, little is known about how these changes are reflected in the attitudes of private implementing agents: The hybridization literature neglects individuals, and street-level bureaucracy research has disregarded hybridization. This article extends Hupe and Hill's () accountability regimes framework to introduce the market as an additional accountability regime alongside state, profession, and society. Using a configurational approach, the article explores how public and private food safety inspectors in Switzerland perceive the multiple norms for behavior stemming from their environment. Results suggest that the plural accountabilities of for-profit street-level bureaucrats can increase the dilemmas involved in their work. Under certain circumstances, for-profit street-level bureaucrats have particular difficulties reconciling rule pressure with market incentives and client demands. The extended accountability regimes framework fruitfully captures such dilemmas and helps identify suitable governance responses.